Sin, the Savior and salvation the theology of everlasting life - Lightner, Robert Paul (Nashville, TN Thomas Nelson, 1991)
Includes bibliographical references and indexes.
Keywords: Salvation (theology).; Sin (theology).; Jesus Christ -- person and offices; Immortality -- biblical teaching